Are There Understanding-Assent Links? - Åsa Wikforss (Baltic International Yearbook of Cognition, Logic and Communication, 2009)
It is commonly held that there are internal links between understanding and assent such that being semantically competent with an expression requires accepting certain sentences as true. The paper discusses a recent challenge to this conception of semantic competence, posed by Timothy Williamson (2007). According to Williamson there are no understanding-assent links of the suggested sort, no internal connection between semantic competence and belief. I suggest that Williamson is quite right to question the claim that being semantically competent with an expression e requires accepting a certain sentence S as true. However, Williamson does not merely wish to reject this version of the understanding-assent view, but the very idea that the connection with belief provides constitutive constraints on linguistic understanding and concept possession. This further move, I argue, is very problematic. Giving a plausible account of semantic competence requires accepting that there are constitutive links between understanding and assent, although these links should be construed holistically rather than atomistically.